TYPES OF SEMANTIC RELATIONS IN LEXICOGRAPHY - Roza Bahodirova,; Madina Baratova, (TADQIQOTLAR, 2026)
Abstract Lexicography is an important branch of linguistics that studies the theory and practice of dictionary making. One of the central aspects of lexicography is semantic relations, which explain how words are connected in meaning. Semantic relations help lexicographers  organize  vocabulary,  define  meanings  accurately,  and  improve  the quality of dictionaries. This article discusses the main types of semantic relations used in lexicography, including synonymy, antonymy, hyponymy, meronymy, polysemy, homonymy,  and  collocation.  The  study  also  explains  the  importance  of  semantic relations in language learning, communication, and modern dictionary compilation. Semantic  analysis  provides  valuable  support  for  both  traditional  and  digital lexicography because it allows dictionaries to present lexical information in a more systematic and understandable way.